STRATEGI PENGEMBANGAN DESA WISATA TERHADAP PENINGKTAN EKONOMI MASYARAKAT DI DESA PURBA MANALU, KABUPATEN HUMBANG HASUNDUTAN - Ompusunggu, Vina Maria; Sitorus, Ramcan Agustinus; Manalu, Leonardo (JURNAL REGIONOMIC, 2024)
The existence of tourism villages currently has a good allure. Not only because Indonesia consists of diverse traditions and cultures, but the natural wealth that stretches from one village to another has its own uniqueness and distinctiveness. one village to another has its own uniqueness and distinctiveness. So when tourists try to know more about one of the tourist villages in Indonesia, of course they will visit. Indonesia, of course they will visit. Village development strategy Manalu Ancient Tourism Village is very important for villages that do not have natural tourism. This is intended so that the Purba Manalu Tourism Village that is developed can survive and continue to increase over time. survive and continue to increase over time. If the Purba Manalu Tourism Village Purba Manalu Tourism Village is well managed, it is hoped that it will help increase the income of the village and especially the residents of the management community as well as the local community. income of the Village and especially the management community and the community around Pahawang Tourism Village. The objectives in this study are to know the strategy of developing a tourist village on economic enhancement community in Purba Manalu village, Humbang Hasundutan Regency. Research method The research method used is qualitative research. In this case the author focuses on research that is seen as a tourist village that has natural potential including mountains, agro, beaches, culture, history, and so on. This tourist village opportunity must prioritize the concept of Unity in Diversity which reflects the diversity of cultures, traditions, natural beauty, crafts and others as an identity which then becomes a concentration of tourist destinations without competition in capturing tourists. In the development of a tourist village in Purba Manalu Village, it has local wisdom values which are the main capital in building human creativity which has economic value and can increase community income without destroying social order and the surrounding natural environment. However, the management of its tourism potential has not been maximized so that it does not attract tourists to visit and the government does not support the development of the tourist village. To overcome these problems, improvements are needed in the arrangement of the area and the development of tourism activities. While the potential activity of natural tourism development is one of the efforts that can be done to improve the quality of natural resources and human resources. In its management activities, it is in accordance with the principles of Community Economy, namely the existence of an honest attitude, does not damage the environment so that it can help improve the community's economy.